Knowledge, Adherence, and Barriers Related to Ventilator-Associated Pneumonia Prevention among Emergency Patients - Ashwaq Ali Asiri , Adel Awwadh Almutairi , Mohammed Saud Al-Otaibi , Saad Abdulrahman Abdullah Aljibreen , Muhannad Alzhrani , Ghaith Abdullah Alqwiz; Zakri Jubran Ahmed Shanyah , Raed Slman Ahmad Sahari , Khalid Ahmed Mohammed Mulayhi , Hawazin saleh Alluhaybi , Ahmed Salem Alghamdi , Abdullah Mohammed Alamri (Migration Letters, 2022)
Background: Ventilator-associated pneumonia (VAP) is the most common complication found among patients who use mechanical ventilation as a life support measure. To improve the quality of nursing practice related to VAP prevention, baseline information regarding knowledge, adherence, and barriers related to VAP prevention among emergency care nurses should be explored. The study aims: To explore knowledge, adherence, and barriers to VAP prevention among emergency care nurses in Jeddah, KSA. The relationship between knowledge and adherence was also determined. Methods: A descriptive correlational design was conducted from January to July 2022. Purposive sampling was used to recruit 142 emergency care nurses from six hospitals in Jeddah, KSA. Measurement tools were composed of 1) the demographic data record form, 2) questionnaires related to knowledge towards prevention of VAP (QKVAP), and 3) the Questionnaire on VAP Prevention Compliance and Barriers (QVAPCB). The Arabic versions of these instruments were used. The internal consistency of the QKVAP using the KR-20 formula was 0.81, and the Cronbach’s alpha coefficients of the QVAPCB adherence and barrier parts were 0.91 and 0.87, respectively. Data were analyzed using descriptive statistics and Spearman’s rank-order correlation test. Results: The results of this study were as follows: The majority of participants (81.69%) had knowledge of VAP and VAP prevention at a fair level; The majority of participants (95.07%) perceived adherence to VAP prevention at a sufficient level; Knowledge was positively related to adherence to VAP prevention at a low level (r = .255, p < .001); The top three barriers towards VAP prevention perceived by emergency care nurses were forgetfulness to perform some evidence-based procedures (90.14%), staff shortages in the unit (82.39%), and noncompliance of patients in performing VAP prevention practice (59.15%). Conclusion: The study findings provide baseline information regarding emergency care nurses’ knowledge and adherence, as well as the barriers to complying with VAP prevention. Further research should explore the factors influencing collaboration on and barriers to VAP prevention related to the use of ventilators in each emergency in order to have strategic plans to improve the VAP prevention.